2014
DOI: 10.1007/s00300-014-1496-8
|View full text |Cite
|
Sign up to set email alerts
|

Composition, abundance and distribution of holoplanktonic polychaetes within the Strait of Magellan (southern America) in austral summer

Abstract: This study enlarge the knowledge on species composition, distribution and community structure of pelagic polychaetes on the basis of finely stratified spatial sampling representing austral summer conditions in the Strait of Magellan. Zooplankton samples were collected in late austral summer 1995. A total of 56,489 pelagic polychaete specimens were collected. Eight holopelagic polychaete taxa were recorded in addition to Spionidae and Terebellidae larvae and reproductive stolons of Autolytinae. Pelagobia longic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…It was reported that the geographical location of holoplanktonic polychaetes can be correlated to productivity and main water masses 14,77,78 , showing assemblages in areas of high primary and secondary production 66,79–84 . All the species found in the present study (except Pedinosoma curtum that represents only the 0.06% of polychaete community) were more abundant in the upper 200 m, and the main part (nineteen of twenty-two species) in the upper 100 m. As already reported, holoplanktonic polychaete species are distributed in the epipelagic region of the water column 5,8,9,71,85,86 , most probably because this layer is characterized by a large supply of food, with highest concentration of phytoplankton, microzooplankton and copepods 87,88 . Surely, the most important gas in water is oxygen, as its role in metabolic processes is essential to all forms of life and it affects the distribution of pelagic organisms at several spatial scales 12 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It was reported that the geographical location of holoplanktonic polychaetes can be correlated to productivity and main water masses 14,77,78 , showing assemblages in areas of high primary and secondary production 66,79–84 . All the species found in the present study (except Pedinosoma curtum that represents only the 0.06% of polychaete community) were more abundant in the upper 200 m, and the main part (nineteen of twenty-two species) in the upper 100 m. As already reported, holoplanktonic polychaete species are distributed in the epipelagic region of the water column 5,8,9,71,85,86 , most probably because this layer is characterized by a large supply of food, with highest concentration of phytoplankton, microzooplankton and copepods 87,88 . Surely, the most important gas in water is oxygen, as its role in metabolic processes is essential to all forms of life and it affects the distribution of pelagic organisms at several spatial scales 12 .…”
Section: Discussionsupporting
confidence: 82%
“…Holoplanktonic polychaetes are common in marine zooplankton 3 , although they are not highly important in terms of abundance 5 . Some species may, at times, be the dominant forms in the plankton community 68 . They are widely distributed in the oceans, mainly in the open sea, but they also occur in neritic region 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Polygordius exolarvae living in the neustonic layer of a number of estuarine sites along the southern Chilean coast were studied. This finding is the first reference of Polygordius in southern Chile, despite a large body of research on polychaete in benthic (Rozbaczylo, 1985;Cañete et al 1999;Cañete et al 2010;Ortiz & Quiroga, 2010;Cañete et al 2012) and pelagic samples (Defren-Janson et al 1999;Fernández-Severini & Hoffmeyer, 2005;Aguirre et al 2012;Guglielmo et al 2014;Palma et al 2014;Cañete et al 2016). This slow confirmation mirrors the history for other specific assignations of Polygordius larvae.…”
Section: Discussionmentioning
confidence: 71%
“…This species was the most numerically dominant species of the identified copepods, in addition to being the most dominant taxa of the neuston. These findings have not been previously reported, possibly due to the use of large net meshes (generally >200 µm) (Mazzocchi et al, 1995;Antezana, 1999;Defren-Janson et al, 1999;Marín & Delgado, 2001;Biancalana et al, 2007;Guglielmo et al, 2014). M. rosea copepodits may only inhabit surface layers of the water column, which would be mostly missed by vertical tows (Kršinić & Grbeco, 2012).…”
Section: Presence Of Microsetella Rosea In Western Magellan Watersmentioning
confidence: 71%